Application of Learning Theories in Online Instructional Environments and Materials: A Study for Developing a Set of Criteria - Şanal, Seda Özer; Akçay, Arif; Tutulmaz, Meral; Mukaddes, Erdem (My University, 2019)
The aim of this study was to develop a set of agreed criteria for the examination or formation of online instructional environments and materials from the viewpoint of learning theories. Based on the understanding that the guidance of learning theories is needed in all stages of an instructional design process from planning to implementation, this study first examined the behaviourist, cognitive, and constructivist learning theories about learning. Instructional practice examples were then examined to determine statements showing how these explanations reflect on the instructional environments or materials. The first statements revised in line with the expert opinions were turned into a 5-point Likert type scale. The opinions of the experts were received on the scale and the necessary revisions were made. Using the 70-item scale, six different open access instructional materials from the Educational Informatics Network (EBA) were examinedContent validity indices were calculated based on the opinions of 26 experts for the final scale, for which the acceptable levels of conformity were determined. At the end of the final review, a set of criteria consisting of 60 items was developed.
Keywords: Eğitim; Eğitim Araştırmaları; Bilgisayar Bilimleri; Bilgi Sistemleri